Development of an Optical Sensor Head for Current and Temperature Measurements in Power Systems. (17th April 2013) - de Nazaré, Fábio V. B.; Werneck, Marcelo M.; de Oliveira, Rodrigo P.; Santos, D. M.; Allil, R. C.; Ribeiro, B. A.
Abstract : The development of a current and temperature monitoring optical device intended to be used in high-voltage environments, particularly transmission lines, is presented. The system is intended to offer not only measurement reliability, but to be also practical and light weighted. Fiber Bragg gratings (FBGs) are employed in the measurement of both physical parameters: the current will be acquired using a hybrid sensor head setup—an FBG fixed on a magnetostrictive rod—while a single-point temperature information is provided by a dedicated grating. An inexpensive and outdoor-suitable demodulation method, such as the fixed filter technique, should be used in order to improve the instrumentation robustness, avoiding expensive and complex auxiliary electronics. The preliminary results for laboratory tests are also discussed.